2016
DOI: 10.1371/journal.pone.0155166
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Flood-Related Diseases of Eyes, Skin and Gastrointestinal Tract in Taiwan: A Retrospective Cohort Study

Abstract: Floods are known to cause serious environmental damage and health impacts. Studies on flood-related diseases have been primarily on individual events, and limited evidence could be drawn on potential health impacts from floods using large population data. This study used reimbursement records of one million people of the Taiwan National Health Insurance program to compare incident diseases of the eyes, skin and gastrointestinal (GI) tract associated with floods. Incidence rates for the selected diseases were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 35 publications
0
14
0
1
Order By: Relevance
“…Scabies infestation by Sarcoptes scabiei is transmitted via direct skin‐to‐skin contact and was the leading cause of morbidity in the flooding in Baluchistan, Pakistan . Scabies appears as multiple pruritic erythematous papules with excoriations with predilection on the interdigital web spaces of hands and feet, volar wrists, umbilicus, areolae, and genital areas (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Scabies infestation by Sarcoptes scabiei is transmitted via direct skin‐to‐skin contact and was the leading cause of morbidity in the flooding in Baluchistan, Pakistan . Scabies appears as multiple pruritic erythematous papules with excoriations with predilection on the interdigital web spaces of hands and feet, volar wrists, umbilicus, areolae, and genital areas (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a massive outbreak of leptospirosis, an infectious disease caused by the pathogenic bacteria Leptospira spp., occurred following the historical flood caused by Typhoon Ondoy in 2009, in Manila and its surrounding cities, which resulted in 3389 cases and 249 deaths [27]. An epidemiological study showed that urban flooding events increased cases of gastroenteritis in Taiwan [28].…”
Section: Health Risk Of Waterborne Infectious Diseases Related To Urbmentioning
confidence: 99%
“…2,3 Due to changes in environmental sanitation, overcrowded shelters, poor personal hygiene, poor nutrition and deterioration of drinking water supply, there is increased risk of infectious diseases. 4 Various studies have reported the increased risks of waterborne and vector-borne diseases from exposure to contaminated water and materials during the flood and in the post-flood cleanup process. The diseases of eyes, skin, soft tissue, gastrointestinal diseases, respiratory tract infections and vector-borne infectious diseases are reported to increase during and after the flood.…”
Section: Introductionmentioning
confidence: 99%
“…The diseases of eyes, skin, soft tissue, gastrointestinal diseases, respiratory tract infections and vector-borne infectious diseases are reported to increase during and after the flood. [2][3][4][5][6][7][8] Nepal is a low-income country with tremendous geographical diversity. Nepal can be divided along a south-to-north transect into three belts: Terai, Pahad and Himal.…”
Section: Introductionmentioning
confidence: 99%